Monitoring Agricultural Land Changes in Peri-Urban Oran, Algeria: A Mixed Methods Analysis - Rabia Samah Choukri; Tarik Ghodbani; Muhammad Salem (The Journal of Engineering and Exact Sciences)
The dynamics of agricultural land change in peri-urban areas are critical due to their significant impacts on agricultural productivity, food security, sustainable development, and socio-economic dynamics. These intricate processes require a robust methodological approach that can effectively identify, quantify, and analyze the drivers behind land-use changes. In the peri-urban areas of Oran, Algeria, the rapid conversion of agricultural land, particularly along the main highways in the south and southwest regions, underscores the urgent need for focused research. This study aims to map and analyze agricultural land changes between 1998 and 2019, exploring the underlying factors contributing to these shifts. Employing a mixed methods approach, the study integrates both quantitative and qualitative data to provide a comprehensive understanding of the phenomenon. The methodology encompasses five main tasks: (1) data collection and identification of significant temporal markers, (2) implementation of a Random Forest classification using medium resolution Landsat imagery, (3) assessment of the extent and patterns of agricultural land changes, (4) Evaluation of relevant planning documents, (5) field work, including stakeholders interviews and focus groups. The results reveal a persistent increase in built-up areas over the study period, leading to a corresponding decline in agricultural land. This pattern highlights emerging land-use conflicts among stakeholders. The study offers valuable insights for policymakers, suggesting strategies for more effective land use management, and the promotion of sustainable agricultural practices.